The implementation of monitorial system in a public university in China: A qualitative research - Guo, Jing (2021)
The main objective of this case study is to examine the implementation of the student monitorial system (SMS) and its benefits. In this qualitative study, the experiences of six students, four monitors and two lecturers were explored through in-depth semi-structured interviews as the primary data collection method concerning the phenomenon under study. Open-ended questions were asked based on research questions of this study, and participants were encouraged to discuss their experiences in depth. Thematic analysis was used to analyse the data to identify themes from the data obtained from the interview. The findings revealed that all twelve participants indicated positive perceptions and satisfaction in their descriptions of the implementation of the monitorial system and benefits of SMS. Aside from that, the findings also revealed the deficiencies of the implementation of student monitorial system.